Nitinol Stent Implantation in the Superficial Femoral Artery and Proximal Popliteal Artery: Twelve-Month Results From the Complete SE Multicenter Trial. (April 2014) - Laird, John R.; Jain, Ash; Zeller, Thomas; Feldman, Robert; Scheinert, Dierk; Popma, Jeffrey J.; Armstrong, Ehrin J.; Jaff, Michael R.
Purpose: To determine the safety and efficacy of a new-generation nitinol stent with enhanced flexibility in arterial lesions in the superficial femoral artery (SFA) and proximal popliteal artery (PPA). Methods: The Complete Self-Expanding (SE) Multicenter Trial ( ClinicalTrials.gov identifier NCT00814970) enrolled 196 patients (124 men; mean age 68.7±10.5 years) from 28 centers in the United States and Europe. The patients presented with intermittent claudication (193/196) or ischemic rest pain (3/196) and were treated with nitinol stents for obstructive lesions of the SFA or PPA. Over a quarter of lesions (29.9%) were chronic total occlusions. The mean lesion length was 60.7 mm. Moderate to severe calcification was present in 91.0% of lesions. Results: A total of 225 stents were successfully implanted in 213 (99.5%) of 214 lesions. Acute lesion success (<30% residual stenosis) was achieved in 90.0%. There were no in-hospital major adverse events. Primary patency (defined as a peak systolic velocity ratio <2.0) at 12 months was 72.6%. Clinically-driven target lesion revascularization (TLR) was required in 8.4% of patients at 12 months. The mean ankle-brachial index increased from 0.7 at baseline to 0.9, and there was sustained improvement in the Rutherford category, with 83% of patients classified as Rutherford category 0 or 1 at 12-month follow-up. No stent fractures were detected through 12 months. Conclusion: In this multicenter trial, primary implantation of a new-generation self-expanding nitinol stent in the SFA and PPA was associated with a low rate of TLR and sustained clinical benefit at 12 months without stent fracture.